1986
DOI: 10.1111/j.1532-5415.1986.tb07262.x
|View full text |Cite
|
Sign up to set email alerts
|

Skills Training With Supporters of the Demented

Abstract: This study examined the effects of Supporter Endurance Training (SET) on family supporters of elderly demented patients. Single case methodology was used in evaluating the outcome of providing eight supporters with eight weekly training sessions in meditative relaxation and assertiveness. Four such supporters received no special training. A videotape dramatizing typical problem situations encountered with a demented family member was used to elicit information about supporters' coping styles. Post-training and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
2

Year Published

1991
1991
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 20 publications
1
9
0
2
Order By: Relevance
“…Selection of elements for the present training programme was made on the basis of the literature and a survey (conducted by KR) of the membership of the Alzheimer's Association. The findings of this survey confirmed a number of reported strategies and identified caregivers' needs as: a wish to understand the disease, its progress and its limitations (Barnes et al, 1981;; a desire to learn more about specific technical aspects of Alzheimer's disease (Fortinsky and Hathaway, 1990); and need for assistance with problem-solving skills (Gendron et al, 1986;Haley ef al., 1987). The survey results of caregiver needs were prioritized and developed as the core components of the training programme.…”
Section: H Brodaty K Roberts a N D K Peterssupporting
confidence: 72%
“…Selection of elements for the present training programme was made on the basis of the literature and a survey (conducted by KR) of the membership of the Alzheimer's Association. The findings of this survey confirmed a number of reported strategies and identified caregivers' needs as: a wish to understand the disease, its progress and its limitations (Barnes et al, 1981;; a desire to learn more about specific technical aspects of Alzheimer's disease (Fortinsky and Hathaway, 1990); and need for assistance with problem-solving skills (Gendron et al, 1986;Haley ef al., 1987). The survey results of caregiver needs were prioritized and developed as the core components of the training programme.…”
Section: H Brodaty K Roberts a N D K Peterssupporting
confidence: 72%
“…The provision of education, peer support, and medical treatment, although of unquestionable value and import, have not addressed the range of needs and concerns caregivers identify at different points in time in their caregiving experience. Alternatively, recent studies have identified skill development as a critical strategy to enhance caregiver problem solving abilities and hence management of daily issues of care, which change over time (Clark & Rakowski, 1983;Gendron et al, 1986;Crossman, London & Barry, 1981;Lovett & Gallagher, 1988;Pinkston & Linsk, 1986;Toseland, Rossiter, & Labrecque, 1989). The focus on caregiver skill building necessitates a delivery approach that is sensitive to the caregiver's perceptions of their own needs, their style of care, and personal values.…”
Section: Significancementioning
confidence: 95%
“…Une étude descriptive (Levine et al, 1983) effectuée sur dix personnes-soutien, dont les patients étaient suivis par le programme de psychogériatrie, nous a permis de constater que certaines d'entre elles, dési-gnées comme «les super copers», semblaient posséder des habiletés particulières qui les aidaient à poursuivre leur rôle durant une plus longue période de temps, et ce, malgré la gravité des symptômes présentés par leur patient. Une seconde étude (Gendron et al, 1986), qui évaluait l'efficacité d'une intervention individuelle (Levine et al, 1983) axée sur l'apprentissage d'habiletés personnelles pouvant aider à lutter contre le stress associé au rôle de soignant, montre l'utilité de ce type de programme, puisque plusieurs des personnessoutien se sont améliorées au niveau de l'affirmation de soi, la résolution de problèmes, la réduction du stress et l'estimation de la prolongation de leur rôle.…”
Section: • Habiletés Personnellesunclassified